Spatial and Temporal Variability in Biochemical Composition, Bacterial Contamination, and Growth of Perna perna in Coastal Waters - Hassan Pyar; Neamah Al-sebaey (Warta Pengabdian Andalas, 2026)
Marine bivalves, particularly the brown mussel Perna perna, constitute a significant source of high-quality protein and essential nutrients for human consumption. This study aimed to evaluate the biochemical composition, bacterial contamination, and growth dynamics of P. perna collected from two coastal locations, Al-Hami and Sharma, along the Gulf of Aden. Proximate analysis revealed that proteins constituted the primary component of mussel tissues, followed by moisture, with lipids, carbohydrates, and ash present in lower proportions. Significant spatial and temporal variations were observed in protein and ash contents (P < 0.05), reflecting the influence of environmental conditions and physiological factors on mussel biochemistry. The estimated energy content underscored the nutritional value of P. perna as a seafood resource. Microbiological assessments detected total coliforms and E. coli in both seawater and mussel tissues, with higher bacterial loads in specific locations, indicating localized contamination likely stemming from anthropogenic activities. Temporal fluctuations in bacterial abundance were also observed, correlating with environmental variables such as temperature and nutrient availability. Growth rate analysis demonstrated moderate variation over the study period, suggesting relatively stable environmental conditions. The integration of biochemical, microbiological, and growth data highlighted the impact of environmental variability on mussel physiology and microbial accumulation. These findings underscore the importance of continuous environmental monitoring to ensure seafood safety, promote sustainable fisheries, and support aquaculture development in coastal regions.